Fe Doped Ga2O3 Nanomaterial Catalysed Green and Efficient One Pot Three Component Synthesis of Tetrahydrobenzo[b]pyran - Parhad, Amol R.; Aute, Dilip S.; Gadhave, Anil G.; Uphade, Bhagwat K. (Letters in Organic Chemistry, 2023)
The present work reports the hydrothermal synthesis of Fe doped gallium oxide nanoparticles and its characterization by IR, XRD, SEM, and EDX techniques. The characterization of Fe doped gallium oxide nanomaterial reveals the 18.58 nm particle size with monoclinic phase. The catalytic activity of nanomaterial was efficiently assessed for one-pot domino Knoevenagel and Michael's addition of different aldehydes, dimedone, and malononitriles to give tetrahydrobenzo [b] pyran derivatives. The remarkable features associated with this green protocol are good to excellent product yields (60-94%), non-chromatographic purification of product, shorter reaction time, and easy work up. The reusability and non-toxic nature of this nanomaterial catalyst escalate the importance of this work.
Keywords: knoevenagel condensation